INSIDER DATA THEFT PREVENTION USING BEHAVIOR PROFILING - Ms.Mayuri M.Bhosale; Mr. G. A. Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
In the commercial organizations especially small and medium scale businesses a lot depends on outsourcing of data which comes with more risk for insider data theft attacks. Insider data theft detection is an emerging field developed with opportunities for new research methodologies. Insider data theft attacks are caused by masquerader stealing a valid user's identification and using it to mimic the authenticate user.